A Medieval Heroine for the Modern Woman: The Fredrika Bremer Association writes women's history (c. 1859–1916). Issue 1 (1st January 2017) - Berglund, Louise
Abstract : This article discusses the history writing of the early liberal women's movement in Sweden, in the Fredrika Bremer Association's journals such as Tidskrift för hemmet and Dagny. Prominent members of the movement sought to create a new history, by women and for women, and to create a pantheon of foremothers and examples for the modern woman. Medieval women were particularly favoured as they could be described in ways that harmonized well with the overall objectives of the liberal women's movement and with the self-images of these early feminists. Thus, individuals such as Saint Birgitta and Queen Philippa were given heroine's portraits and presented as carriers of ideal characteristics. This was a means of positioning themselves and of proving that women were fit to rule and to take active part in political and social life.